Coercive Control: Update and Review. (January 2019) - Stark, Evan; Hester, Marianne
This article reviews the background, introduction, and critical response to new criminal offenses of coercive control in England/Wales and Scotland. How the new Scottish offense is implemented will determine whether it can overcome the shortcomings of the English law. We then review new evidence on four dimensions of coercive control: the relationship between "control" and "violence, " coercive control in same-sex couples, measuring coercive control, and children's experience of coercive control. Coercive control is not a type of violence. Indeed, level of control predicts a range of negative outcomes heretofore associated with physical abuse, including post-separation violence and sexual assault; important differences in coercive control dynamics distinguish male homosexual from lesbian couples; measuring coercive control requires innovative ways of aggregating and categorizing data; and how children experience coercive control is a problem area that offers enormous promise for the years ahead.